Classroom Interaction Analysis Viewed from Information Sources at SMAN 2 Singaraja - ., Ni Made Budi Artati; ., Prof. Dr. Dewa Komang Tantra, M.Sc.; ., Kadek Sonia Piscayanti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at analyzing the implementation of classroom interaction characteristics in writing at SMAN 2 Singaraja viewed from information sources and the description of constrains were found in implementing multi-way interaction in writing at SMAN 2 Singaraja viewed from information sources. The subject of the study were a teacher and 34 students.Kata Kunci : Classroom Interaction, Information Sources This study aimed at analyzing the implementation of classroom interaction characteristics in writing at SMAN 2 Singaraja viewed from information sources and the description of constrains were found in implementing multi-way interaction in writing at SMAN 2 Singaraja viewed from information sources. The subject of the study were a teacher and 34 students.keyword : Classroom Interaction, Information Sources